Traceless Solid-Phase Synthesis of [6,7,8 + 5,6,7]-Fused Molecular Frameworks - Giménez-Navarro, Vanesa; Krchňák, Viktor (Molecules, 2018)
We report two synthetic strategies for traceless solid-phase synthesis of molecular scaffolds comprising 6- to 8-membered rings fused with 5- to 7-membered rings. Traceless synthesis facilitated preparation of target molecules without any trace of polymer-supported linkers. The cyclization proceeded via acid-mediated tandem N-acylium ion formation followed by the nucleophilic addition of O- and C-nucleophiles. The presented synthetic strategy enabled, through the use of simple building blocks without any conformational preferences, the evaluation of the predisposition of different combinations of ring sizes to form fused ring molecular scaffolds. Compounds with any combination of [6,7 + 5,6,7] ring sizes were accessible with excellent crude purity. The 8-membered cyclic iminium was successfully fused only with the 5-membered cycle and larger fused ring systems were not formed, probably due to their instability.
Keywords: Polymers; Catalysis; Solid-Phase Synthesis Techniques; Cyclization; cyklizace; stereoizomerie; polymery; techniky syntézy na pevné fázi; katalýza; Stereoisomerism